Keefektifan Model Pembelajaran Kooperatif Tipe Picture And Picture dalam Penguasaan Kosakata Bahasa Mandarin Siswa - Putri, Nurul Eka; Dalle, Ambo; Usman, Misnawaty (Interference: Journal of Language, Literature, and Linguistics, 2021)
Abstract. This research is a One Group Pretest-Posttest Design study which aims to determine the effectiveness of the picture and picture cooperative learning model in the mastery of Mandarin vocabulary for seventh grade students of SMP Frater Makassar. The independent variable in this study is the effectiveness of the picture and picture type of cooperative learning model, while the dependent variable in this study is the mastery of Mandarin vocabulary. The population in this study were students of class VII SMP Frater Makassar with a total of eight classes with a total of 250 students. The research sample is random sample (random sampling). Of the eight classes, VII A was selected as the experimental class and VII B as the control class, with 30 students each. The data from this research were obtained by providing a written pre-test and post-test with the material "Introduction". The result of t-test calculation at the significant level of 0.05 obtained the value of tcount = 6.22, which is greater than ttable 2.002, so it can be concluded that the picture and picture type of cooperative learning model is effective in mastering Mandarin vocabulary in class VII students of SMP Frater Makassar. The application of the picture and picture type of cooperative learning model can improve the learning of Chinese vocabulary in students, because this model is an educational model that makes pictures as a medium in the learning process so that it can attract students' attention and interest in mastering Mandarin vocabulary.